THE EFFECT OF TECHNOLOGY ACCEPTANCE MODEL, ELECTRONIC WORD OF MOUTH (EWOM) AND SERVICE QUALITY IN APPLICATION CONTACT CENTER NTMC KORLANTAS POLRI ON THE LEVEL OF SATISFACTION - Khairunnisa, Ana; Prasojo, Eko (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2020)
Traffic accident data that occurred in the last three years increased quite significantly from 2017 to 2018 by 5%, and the increase from 2018 to 2019 was 7%. Cases on this highway should be suppressed or even eliminated with an understanding of the safety of the community, especially motorists. One of the government's efforts to provide services to the community in the prevention and management of accidents, the National Traffic Management Center Polri which was later referred to as the NTMC Polri. Implementation of information technology is expected to provide positive and useful services. The purpose of this study was to analyze the effect of acceptance of the use of technology, Electronic Word of Mouth, Service Quality on the NTMC Contact Center application for the NTMC Korlantas Polri on the level of satisfaction. This type of research used in this research is quantitative explanatory. This research was conducted on the application of the NTMC Contact Center Korlantas Polri. The population in this study were 10,000 people who had accessed and used the NTMC application for public complaint service needs. The research sample was taken by using snowball sampling with the Slovin formula to obtain a sample of 100 people. Data analysis in this study used multiple linear regression analysis. The results showed that the technology acceptance model variable had a positive and significant effect on community satisfaction with a t-value of 3,120> t table, 2,000 with a sig value of 0,000. Furthermore, the variable electronic word of mouth has no effect on community satisfaction with t-count value of 1.156 t table, 2,000 with a sig value of 0.000. Keywords: Electronic Word of Mouth, Technology Acceptance Model